(untitled) (Baghdad Science Journal, 2025)
The electrical insulation of the manufacture sulfonated phenol-formaldehyde viscous material (product) has been studied with Polyvinyl-acetate (PVA) and toluene diisocyanate (TDI) blend has been prepared by fixing percentage by weight 3:1 and mixed with different percentages by weight of the product sulfonated phenol formaldehyde viscous mass (SPF). The Fourier transform infrared (FTIR) spectroscopy is done on (SPF) resin powder and prepared film of PVA-TDI-SPF viscous mass. The quality factor (Q), dissipation factor (D), parallel resistance (Rp), series resistance (Rs), parallel capacitance (Cp), series capacitance (Cs) and phase shift (?) are measured. The calculated maximum dielectric constant (??) is 3.49x107 at sample (1) wt.1% SPF viscous mass to the weight of (PVA-TDI), the minimum dielectric constant is 1.12x106 at sample (3) wt.3% of SPF viscous mass to PVA-TDI weight. The maximum dielectric loss factor (??) is 3.68x107 at sample (1) and the minimum dielectric loss is 2.04x106 for sample (3). The maximum conductance is 1.06x10-4 S at sample (1) and minimum conductance is 6.64x10-6 at sample (3). The maximum frequency dependent ac. conductivity (?ac) is 2.048 S m-1 for sample (1) and the minimum is 0.113 S m-1 at sample (3). The maximum total conductivity (?t) is 126.2 S m-1 for sample (1) and minimum (?t) is 1.129 S m-1 for sample (3). The maximum independent conductivity (?dc) is 124 S m-1 for sample (1) and minimum value is 1.015 S m-1 for sample (3). The maximum capacitive reactance (Xs) is 0.83 M? at sample (5) wt.5% SPF viscous mass to PVA-TDI weight and the minimum is 0.14 M? for sample (3).